RNA methylation in plants: An overview - Shinde, Harshraj; Dudhate, Ambika; Kadam, Ulhas S.; Hong, Jong Chan (Frontiers in Plant Science, 2023)
RNA methylation is an important post-transcriptional modification that influences gene regulation. Over 200 different types of RNA modifications have been identified in plants. In animals, the mystery of RNA methylation has been revealed, and its biological role and applications have become increasingly clear. However, RNA methylation in plants is still poorly understood. Recently, plant science research on RNA methylation has advanced rapidly, and it has become clear that RNA methylation plays a critical role in plant development. This review summarizes current knowledge on RNA methylation in plant development. Plant writers, erasers, and readers are highlighted, as well as the occurrence, methods, and software development in RNA methylation is summarized. The most common and abundant RNA methylation in plants is N6-methyladenosine (m6A). In Arabidopsis, mutations in writers, erasers, and RNA methylation readers have affected the plant’s phenotype. It has also been demonstrated that methylated TRANSLATIONALLY CONTROLLED TUMOR PROTEIN 1-messenger RNA moves from shoot to root while unmethylated TCTP1-mRNA does not. Methylated RNA immunoprecipitation, in conjunction with next-generation sequencing, has been a watershed moment in plant RNA methylation research. This method has been used successfully in rice, Arabidopsis, Brassica, and maize to study transcriptome-wide RNA methylation. Various software or tools have been used to detect methylated RNAs at the whole transcriptome level; the majority are model-based analysis tools (for example, MACS2). Finally, the limitations and future prospects of methylation of RNA research have been documented.